Decolonizing the Spirit in Education and Beyond: Resistance and Solidarity - Wane, Njoki Nathani; Todorova, Miglena S; Todd, Kimberly L (Palgrave Macmillan, 2021)
This multidisciplinary collection probes ways in which emerging and established scholars perceive and theorize decolonization and resistance in their own fields of work, from education to political and social studies, to psychology, medicine, and beyond
Keywords: 1-Cinéma; 1-Histoire de l'art; 1-Jeux vidéo; 1-TV; 2-Pédagogie décoloniale; 2-Théories et épistémologie postcoloniales et décoloniales; 3-Afrique (corpus analysé); 3-Amérique centrale (corpus analysé); 3-Amérique du Nord (corpus analysé); 3-Amérique du Sud (corpus analysé); 3-Asie (corpus analysé); 3-Europe (corpus analysé); 3-Océanie (corpus analysé); 5-Auteur.rice; 5-Auteur.rice PANDC; 5-Auteur.rice autochtone; 5-Auteur.rice noir.e; 5-Autrice; _Nettoyé

Contemporary Indigenous Arts in the Classroom - Garneau, David; Nadeau, Stephanie; Dumais, Doug; Cross, Wahsontiio (Galerie d'art d'Ottawa = Ottawa Art Gallery, 2018)
Keywords: 1-Histoire de l'art; 2-Pédagogie décoloniale; 2-Épistémologies autochtones; 3-Amérique du Nord (corpus analysé); 4-Amérique du Nord (lieu de production du savoir); 5-Auteur.rice autochtone; 5-Autrice; _Nettoyé

Paix, pouvoir et droiture. Un manifeste autochtone - Alfred, Taiaiake (Éditions Hannenorak, 2014)
Paix, pouvoir et droiture : un manifeste autochtone, qui tire sa structure des chants rituels de la cérémonie de condoléances rotinohshonni, appelle toutes les Premières Nations à prêter attention aux messages des ancêtres afin de développer une philosophie visant à contrer l'assimilation. L'essai de Taiaiake Alfred est un véritable plaidoyer en faveur de droits et de l'autodétermination des peuples autochtones. Ce manifeste se veut avant-gardiste proposant des pistes de réflexion inédites ayant significativement participé à améliorer la compréhension des enjeux des Première Nations de l'Amérique du Nord.
Keywords: 1-Cinéma; 1-Histoire de l'art; 1-Jeux vidéo; 1-TV; 2-Méthodologie de recherche décoloniale; 2-Pédagogie décoloniale; 2-Théories et épistémologie postcoloniales et décoloniales; 2-Épistémologies autochtones; 3-Amérique du Nord (corpus analysé); 4-Amérique du Nord (lieu de production du savoir); 5-Auteur.rice autochtone; _Nettoyé

Indigenous and Decolonizing Studies in Education: Mapping the Long View - Tuhiwai Smith, Linda; Tuck, Eve; Yang, K. Wayne (Indigenous and decolonizing studies in education, 2019)
Indigenous and decolonizing perspectives on education have long persisted alongside colonial models of education, yet too often have been subsumed within the fields of multiculturalism, critical race theory, and progressive education. Timely and compelling, Indigenous and Decolonizing Studies in Education features research, theory, and dynamic foundational readings for educators and educational researchers who are looking for possibilities beyond the limits of liberal democratic schooling. Featuring original chapters by authors at the forefront of theorizing, practice, research, and activism, this volume helps define and imagine the exciting interstices between Indigenous and decolonizing studies and education. Each chapter forwards Indigenous principles - such as Land as literacy and water as life - that are grounded in place-specific efforts of creating Indigenous universities and schools, community organizing and social movements, trans and Two Spirit practices, refusals of state policies, and land-based and water-based pedagogies.--publisher's description.
Keywords: 1-Cinéma; 1-Histoire de l'art; 1-Jeux vidéo; 1-TV; 2-Pédagogie décoloniale; 2-Théories et épistémologie postcoloniales et décoloniales; 2-Épistémologies autochtones; 3-Amérique du Nord (corpus analysé); 3-Océanie (corpus analysé); 4-Amérique du Nord (lieu de production du savoir); 4-Océanie (lieu de production du savoir); 5-Auteur.rice autochtone; 5-Autrice; _Nettoyé

Imágenes de lo extraordinario. Memorias de un continente poblado por monstruos. - Gil, Slenka Leandra Botello; Camacho, Daianna Sierra (Cuadernos de Música, Artes Visuales y Artes Escénicas, 2021)
Este trabajo presenta los resultados de la investigación Imágenes de lo extraordinario: monstruos americanos del siglo XVI, proceso de creación artística desarrollado por los estudiantes del Semillero de Investigación en Artes Visuales (SINAV) del programa de Artes Visuales de la Universidad Nacional Abierta y a Distancia (UNAD) entre 2018 y 2019. Para analizar de manera crítica e histórica la construcción de identidades sobre lo latinoamericano, se tomó como marco de análisis la representación de lo monstruoso en los relatos y las imágenes construidas por los cronistas de Indias en el siglo XVI, los cuales marcaron procesos de marginalización cultural, construcción de subjetividades y dinámicas de poder, y presentaron al habitante americano como una otredad que estaba fuera de los límites de la cultura dominante occidental. Se presentan los postulados teóricos sobre lo monstruoso como marco para el análisis histórico y la creación de obra, con una metodología de trabajo colaborativo y en gran parte virtual. Posteriormente, se exponen algunos resultados de la investigación histórica que dan paso a detallar el proceso de creación de obra que culminó con la exposición de la instalación audiovisual Imágenes de lo extraordinario, así como con una amplia serie de ilustraciones contemporáneas sobre lo monstruoso y un producto digital en formato página web donde se presenta una cartografía de lo monstruoso en América Latina y se recogen las memorias de todo el proyecto. This work presents the results of the research Images of the Extraordinary: American Monsters of the 16th Century, artistic creation process developed by the students of the Research Seedbed in Visual Arts (SINAV, for its initials in Spanish) of the Visual Arts program of Universidad Nacional Abierta y a Distancia (UNAD) between 2018 and 2019. With the objective of analyzing, in a critical and historical way, the construction of identities on Latin American matters, the representation of the monstrous in the stories and images constructed by the chroniclers of the Indies in the 16th century was used as a framework of analysis. These chroniclers marked processes of cultural marginalization, construction of subjectivities and power dynamics, and presented the American inhabitant as an otherness that was outside the limits of the dominant Western culture. The theoretical postulates about the monstrous are presented as a framework for historical analysis and the creation of works, with a collaborative and largely virtual working methodology. Some results of the historical research are then presented, which gives way to detailing the process of creating work that culminated in the exhibition of the audiovisual installation Images of the Extraordinary, as well as a wide range of contemporary illustrations on the monstrous and a digital product in web page format where a cartography of the monstrous in Latin America is presented and the memories of the whole project are collected.
Keywords: 1-Histoire de l'art; 2-Histoire/Historiographie critique; 2-Méthodologie de recherche décoloniale; 2-Pédagogie décoloniale; 2-Théories et épistémologie postcoloniales et décoloniales; 2-Étude des représentations; 3-Amérique centrale (corpus analysé); 3-Amérique du Nord (corpus analysé); 3-Amérique du Sud (corpus analysé); 4-Amérique du Sud (lieu de production du savoir); _Nettoyé

Transformations and Remembrances in the Digital Game We Sing for Healing - LaPensee, Elizabeth A. (Transmotion, 2017)
Digital games, with their capacity for expression and facilitating experience through code, design, art, and audio, offer spaces for Indigenous creatives to contribute to Gerald Vizenor’s characterization of survivance as an active sense of Native presence. Indigenous digital games can be acts of survivance both in the ways they are created as well as the resulting designs. We Sing for Healing is an experiment in developing an Indigenous digital game during limited Internet access that resulted in a musical choose-your-own adventure text game with design, art, and code by Anishinaabe, Métis, and Irish game developer Elizabeth LaPensée alongside music by Peguis First Nation mix artist Exquisite Ghost. The non-linear gameplay expresses traditional storytelling patterns while enabling players to poetically travel in, through, and around traditional teachings. The design uses listening, choosing, and revisiting to reinforce what is best described as a non-linear loopular journey.
Keywords: 1-Jeux vidéo; 2-Humanités numériques; 2-Pédagogie décoloniale; 2-Recherche-création; 2-Épistémologies autochtones; 3-Amérique du Nord (corpus analysé); 4-Amérique du Nord (lieu de production du savoir); 5-Auteur.rice autochtone; 5-Autrice; 5-Créateur.rice autochtone; 5-Créatrice; _Nettoyé

Honour water: Gameplay as a Pathway to Anishinaabeg Water Teachings - LaPensée, Elizabeth (Decolonization: Indigeneity, Education & Society, 2018)
Digital games can uniquely express Indigenous teachings by merging design, code, art, and sound. Inspired by Anishinaabe grandmothers leading ceremonial walks known as Nibi Walks, Honour Water (http://www.honourwater.com/) is a singing game that aims to bring awareness to threats to the waters and offer pathways to healing through song. The game was developed with game company Pinnguaq and welcomes people from all over to sing with good intentions for the waters. The hope is to pass on songs through gameplay that encourages comfort with singing and learning Anishinaabemowin. Songs were gifted by Sharon M. Day and the Oshkii Giizhik Singers. Sharon M. Day, who is Bois Forte Band of Ojibwe and one of the founders of the Indigenous Peoples Task Force, has been a leading voice using singing to revitalize the waters. The Oshkii Giizhik Singers, a community of Anishinaabekwe who gather at Fond du Lac reservation, contribute to the healing for singers, communities, and the waters. Water teachings are infused in art and writing by Anishinaabe and Métis game designer, artist, and writer Elizabeth LaPensée. From development to distribution, Honour Water draws on Indigenous ways of knowing to reinforce Anishinaabeg teachings with hope for healing the water.
Keywords: 1-Jeux vidéo; 2-Humanités numériques; 2-Pédagogie décoloniale; 2-Recherche-création; 2-Épistémologies autochtones; 3-Amérique du Nord (corpus analysé); 4-Amérique du Nord (lieu de production du savoir); 5-Auteur.rice autochtone; 5-Autrice; 5-Créateur.rice autochtone; 5-Créatrice; _Nettoyé

“I see my ancestors”: Exploring Tribal College Student Experiences Playing When Rivers Were Trails - Emmons, Nichlas; LaPensee, Elizabeth (AlterNative: An International Journal of Indigenous Peoples, 2021)
The educational video game, When Rivers Were Trails, was launched in 2019. The purpose of the game is to teach players about Indigenous perspectives of history, US federal allotment policies affecting tribal nations, and some of the effects of these policies on Indigenous peoples. This article explores tribal college student experiences playing When Rivers Were Trails in hopes that it provides the basis for further research into how tribal college faculty may be able to teach the game within their own classrooms. Tribal colleges and universities were created by tribal nations to provide for the higher education needs of their citizens. Using phenomenological research methods, seven college students volunteered to participate in a brief study about their experiences playing the video game. Upon transcription and analysis of the interview data, three themes were developed that capture how these students define their experience with When Rivers Were Trails: feelings of representation, histories of land dispossession, and resilience of communities.
Keywords: 1-Jeux vidéo; 2-Approches sociologiques; 2-Humanités numériques; 2-Pédagogie décoloniale; 2-Épistémologies autochtones; 2-Étude de la réception; 2-Étude des représentations; 3-Amérique du Nord (corpus analysé); 4-Amérique du Nord (lieu de production du savoir); 5-Auteur.rice autochtone; 5-Autrice; 5-Créateur.rice autochtone; 5-Créatrice; _Nettoyé

Towards Sovereign Games - LaPensée, Elizabeth A.; Laiti, Outi; Longboat, Maize (Games and Culture, 2021)
Video games can be dynamic sovereign spaces for Indigenous representation and expression when the self-determination of Indigenous people is supported. Where ga...
Keywords: 1-Jeux vidéo; 2-Humanités numériques; 2-Pédagogie décoloniale; 2-Épistémologies autochtones; 3-Amérique du Nord (corpus analysé); 4-Amérique du Nord (lieu de production du savoir); 4-Europe (lieu de production du savoir); 5-Auteur.rice autochtone; 5-Autrice; _Nettoyé

Thunderbird Strike: Survivance in/of an Indie Indigenous Game - LaPensée, Elizabeth (Video Game Art Reader 2.1, 2018)
Thunderbird Strike, a 2D side-scroller developed by Elizabeth LaPensée, allows a player fly from the Tar Sands to the Great Lakes as a thunderbird protecting Turtle Island with searing lightning against the snake that threatens to swallow the lands and waters whole. The game encouraged players to learn about the indigenous culture, reflect on water protection and alternative energy sources, and gain awareness of risks posed by oil pipeline construction for the conveyance of tar sands.Thunderbird Strike was developed through residencies including O k’inādās Residency, The Banff Musicians in Residence Program, and Territ-Aur(i)al Imprints Exchange thanks to the 2016 Artist Fellowship grant from the Arrowhead Regional Arts Council.
Keywords: 1-Jeux vidéo; 2-Humanités numériques; 2-Pédagogie décoloniale; 2-Recherche-création; 2-Épistémologies autochtones; 3-Amérique du Nord (corpus analysé); 4-Amérique du Nord (lieu de production du savoir); 5-Auteur.rice autochtone; 5-Autrice; 5-Créateur.rice autochtone; 5-Créatrice; _Nettoyé

When Rivers Were Trails: Cultural Expression in an Indigenous Video Game - LaPensée, Elizabeth (International Journal of Heritage Studies, 2021)
When Rivers Were Trails is a 2D adventure game wherein The Oregon Trail meets Where the Water Tastes Like Wine through an Indigenous lens. The game depicts a myriad of cultures during the player’s journey from Minnesota to California amidst the impact of land allotment in the 1890s. Initiated by the Indian Land Tenure Foundation, the game was developed in collaboration with the Games for Entertainment and Learning Lab at Michigan State University thanks to support from the San Manuel Band of Mission Indians and the many Indigenous creatives who contributed design, art, music, and writing. Uniquely, When Rivers Were Trails is a sovereign game, meaning that it was directed and informed by Indigenous creatives who maintained the role of final decisions during development. Merging design research and close reading methods, this study sets out to describe the game’s design, development process in regards to the game writing, and the resulting themes which emerged as a result of engaging Indigenous writers in self-determined representations.
Keywords: 1-Jeux vidéo; 2-Histoire/Historiographie critique; 2-Humanités numériques; 2-Pédagogie décoloniale; 2-Épistémologies autochtones; 2-Étude des industries culturelles; 2-Étude des représentations; 3-Amérique du Nord (corpus analysé); 4-Amérique du Nord (lieu de production du savoir); 5-Auteur.rice autochtone; 5-Autrice; 5-Créateur.rice autochtone; 5-Créatrice; _Nettoyé

Le jeu vidéo comme vecteur d’expression du patrimoine culturel des Iñupiats d’Alaska - Hocine, Julien; Deslauriers, Patrick (Emulations - Revue de sciences sociales, 2019)
En 2014, une collaboration entre le studio Upper One Games et des conteurs et aînés iñupiats d’Alaska a mené au lancement du jeu vidéo Kisima Inŋitchuŋa (Never Alone). Ce jeu de plateforme invite à une immersion poétique dans un univers nordique guidée par une trame narrative inspirée d’une légende traditionnelle. Dans une perspective culturelle, les fonctions ludique et documentaire du jeu permettent d’acquérir des connaissances en lien avec les pratiques traditionnelles et la vision du monde des Iñupiats. Ainsi, l’étude exploratoire présentée dans cet article contribue à comprendre les caractéristiques du jeu (design, narration, mécaniques) et les stratégies relevant de sa conception. Les résultats invitent à reconsidérer des représentations dominantes du Grand Nord et soulignent en quoi le jeu vidéo se fait vecteur d’expression du patrimoine culturel, artistique et oral d’un peuple autochtone de l’Arctique.
Keywords: 1-Jeux vidéo; 2-Humanités numériques; 2-Pédagogie décoloniale; 2-Épistémologies autochtones; 3-Amérique du Nord (corpus analysé); 4-Amérique du Nord (lieu de production du savoir); _Nettoyé

Exploring Collaborative Talk Among African-American Middle-School Girls in the Context of Game Design for Social Change - Thomas, Jakita O.; Rankin, Yolanda; Saunders, Quimeka (Journal of Computing Sciences in Colleges, 2019)
Computer Science education research establishes collaboration among students as a key component in learning, particularly its role in pair programming. Furthermore, research shows that girls, an underrepresented population in computing, benefit from collaborative learning environments, contributing to their persistence in CS. However, too few studies examine the role and benefits of collaborative learning, especially collaborative talk, among African-American girls in the context of complex tasks like designing video games for social change. In this exploratory study, we engage 4 dyads of African-American middle school girls in the task of designing a video game for social change, recording the dyads' conversations with their respective partners over an eight-week summer game design experience during the second year of what has now become a six-year study. Qualitative analysis of dyadic collaborative discussion reveals how collaborative talk evolves over time in African-American middle-school girls.
Keywords: 1-Jeux vidéo; 2-Approches sociologiques; 2-Genre et sexualité; 2-Humanités numériques; 2-Pédagogie décoloniale; 3-Amérique du Nord (corpus analysé); 4-Amérique du Nord (lieu de production du savoir); 5-Auteur.rice PANDC; 5-Auteur.rice noir.e; 5-Autrice; _Nettoyé

Mondes profanes: enseignement, fiction et histoire - Éthier, Marc-André 1969-; Lefrançois, David 1976-; Joly-Lavoie, Alexandre; Buysse, Alexandre. (Presses de l'Université Laval, 2018)
"Les bandes dessinées, chansons, films, jeux vidéos, musées, reconstitutions, romans, séries télévisées et voyages occupent de plus en plus de place dans la vie des élèves. Comment exploiter en classe ces biens, loisirs et services culturels d'histoire pour que les élèves posent de mieux en mieux certains actes mentaux que les historiennes et historiens doivent effectuer lorsqu'elles et ils adoptent leur pratique? Pour répondre à cette question, les auteures et auteurs de cet ouvrage explorent les usages scolaires possibles et souhaitables des produits qui ne sont pas associés à l'histoire savante et sur l'exploitation didactique de ce que la Loi québécoise sur les biens culturels désigne comme "?une oeuvre d'art, un bien historique, un monument ou un site historique ... une oeuvre cinématographique, audiovisuelle, photographique, radiophonique ou télévisuelle?". Les auteures et auteurs s'intéressent à des oeuvres qui ne sont pas créées pour l'école, mais qui peuvent néanmoins servir aux enseignantes et enseignants pour faire apprendre l'histoire aux élèves."--Résumé de l'éditeur.
Keywords: 1-Jeux vidéo; 2-Histoire/Historiographie critique; 2-Humanités numériques; 2-Méthodologie de recherche décoloniale; 2-Pédagogie décoloniale; 2-Théories et épistémologie postcoloniales et décoloniales; 2-Étude des représentations; 3-Amérique du Nord (corpus analysé); 4-Amérique du Nord (lieu de production du savoir); 5-Autrice; _Nettoyé; _À analyser; _À nettoyer; _À vérifier-Cinéma; _À vérifier-Histoire de l'art; _À vérifier-Télé

Counter-Hegemonic Commemorative Play: Marginalized Pasts and the Politics of Memory in the Digital Game Assassin’s Creed: Freedom Cry - Hammar, Emil Lundedal (Rethinking History, 2015)
In this article, I argue that digital games hold the potential to influence processes of cultural memory related to past and contemporary forms of marginalization. By bringing cultural memory studies into dialogue with game studies, I account for the ways through which digital games and practices of play might influence historical discourses and memory politics pertaining to marginalized identities. In order to demonstrate this, I conduct an analysis of Assassin’s Creed: Freedom Cry, a digital game which includes representation of the eighteenth-century transatlantic slave trade and its racist systems. This analysis is then contrasted with statements by two critics, Evan Narcisse and Justin Clark, about how Freedom Cry highlights specific marginalized identities and represents the past through the game form. These statements, coupled with my game analysis, make the case for a concept that I term ‘counter-hegemonic commemorative play’. This makes visible a form of potentially cathartic power fantasy within a historical struggle, alongside emphasizing a form of designed recognition of marginalized identities within contemporary historical discourses and memory politics.
Keywords: 1-Jeux vidéo; 2-Histoire/Historiographie critique; 2-Humanités numériques; 2-Pédagogie décoloniale; 2-Théories et épistémologie postcoloniales et décoloniales; 2-Étude des représentations; 3-Amérique du Nord (corpus analysé); 4-Europe (lieu de production du savoir); _Nettoyé

Digital Arabs: Representation in Video Games - Šisler, Vít (European Journal of Cultural Studies, 2008)
This article presents the ways in which Muslims and Arabs are represented and represent themselves in video games. First, it analyses how various genres of European and American video games have constructed the Arab or Muslim Other. Within these games, it demonstrates how the diverse ethnic and religious identities of the Islamic world have been flattened out and reconstructed into a series of social typologies operating within a broader framework of terrorism and hostility. It then contrasts these broader trends in western digital representation with selected video games produced in the Arab world, whose authors have knowingly subverted and refashioned these stereotypes in two unique and quite different fashions. In conclusion, it considers the significance of western attempts to transcend simplified patterns of representation that have dominated the video game industry by offering what are known as 'serious' games.
Keywords: 1-Jeux vidéo; 2-Histoire/Historiographie critique; 2-Humanités numériques; 2-Pédagogie décoloniale; 2-Théories et épistémologie postcoloniales et décoloniales; 2-Étude des représentations; 3-Amérique du Nord (corpus analysé); 3-Europe (corpus analysé); 4-Europe (lieu de production du savoir); _Nettoyé

Native Studies Keywords - Teves, Stephanie N.; Smith, Andrea; Raheja, Michelle H. (Critical issues in indigenous studies, 2015)
"Native Studies Keywords explores selected concepts in Native studies and the words commonly used to describe them, words whose meanings have been insufficiently examined. This edited volume focuses on the following eight concepts : sovereignty, land, indigeneity, nation, blood, tradition, colonialism, and indigenous knowledge. Each section includes three or four essays and provides definitions, meanings, and significance to the concept, lending a historical, social, and political context. Take sovereignty, for example. The word has served as the battle cry for social justice in Indian Country. But what is the meaning of sovereignty? Native peoples with diverse political beliefs all might say they support sovereignty-without understanding fully the meaning and implications packed in the word. The field of Native studies is filled with many such words whose meanings are presumed, rather than articulated or debated. Consequently, the foundational terms within Native studies always have multiple and conflicting meanings. These terms carry the colonial baggage that has accrued from centuries of contested words. Native Studies Keywords is a genealogical project that looks at the history of words that claim to have no history. It is the first book to examine the foundational concepts of Native American studies, offering multiple perspectives and opening a critical new conversation"--Résumé du site web de l'éditeur
Keywords: 2-Méthodologie de recherche décoloniale; 2-Pédagogie décoloniale; 2-Théories et épistémologie postcoloniales et décoloniales; 2-Épistémologies autochtones; 3-Amérique du Nord (corpus analysé); 4-Amérique du Nord (lieu de production du savoir); 5-Auteur.rice autochtone; 5-Autrice; _Nettoyé

Whose Land Is It Anyway?: A Manual for Decolonization - McFarlane, Peter; Schabus, Nicole (Fédération of Post-Secondary Education of BC, 2018)
Whose Land Is It Anyway? A Manual for Decolonization provides a variety of Indigenous perspectives on the history of colonialism, current Indigenous activism and resistance, and outlines the path forward to reconciliation. This audio version features renowned Indigenous writers Taiaiake Alfred, Glen Coulthard, Russell Diabo, Beverly Jacobs, Melina Laboucan-Massimo, Kanahus Manuel, Jeffrey McNeil-Seymour, Pamela Palmater, Shiri Pasternak, Nicole Schabus, Senator Murray Sinclair, and Sharon Venne. The late Arthur Manuel’s writings are read by his grandson, Mahekan Anderson.
Keywords: 2-Histoire/Historiographie critique; 2-Méthodologie de recherche décoloniale; 2-Pédagogie décoloniale; 3-Amérique du Nord (corpus analysé); 4-Amérique du Nord (lieu de production du savoir); 5-Auteur.rice autochtone; 5-Autrice; _Nettoyé

Decolonizing Methodologies: Research and Indigenous Peoples - Tuhiwai Smith, Linda (Zed books, 2012)
To the colonized, the term 'research' is conflated with European colonialism; the ways in which academic research has been implicated in the throes of imperialism remains a painful memory. This essential volume explores intersections of imperialism and research - specifically, the ways in which imperialism is embedded in disciplines of knowledge and tradition as 'regimes of truth.' Concepts such as 'discovery' and 'claiming' are discussed and an argument presented that the decolonization of research methods will help to reclaim control over indigenous ways of knowing and being. Now in its eagerly awaited third edition, this bestselling book includes a co-written introduction features contributions from indigenous scholars on the book's continued relevance to current research. It also features a chapter with twenty-five indigenous projects and a collection of poetry
Keywords: 1-Cinéma; 1-Histoire de l'art; 1-Jeux vidéo; 1-TV; 2-Méthodologie de recherche décoloniale; 2-Pédagogie décoloniale; 2-Théories et épistémologie postcoloniales et décoloniales; 2-Épistémologies autochtones; 3-Amérique du Nord (corpus analysé); 3-Océanie (corpus analysé); 4-Océanie (lieu de production du savoir); 5-Auteur.rice autochtone; 5-Autrice; _Nettoyé

Decolonization is not a Metaphor - Tuck, Eve; K. Wayne Yang (Journal Publishing Services, 2012)
Our goal in this article is to remind readers what is unsettling about decolonization. Decolonization brings about the repatriation of Indigenous land and life; it is not a metaphor for other things we want to do to improve our societies and schools. The easy adoption of decolonizing discourse by educational advocacy and scholarship, evidenced by the increasing number of calls to “decolonize our schools,” or use “decolonizing methods,” or, “decolonize student thinking”, turns decolonization into a metaphor. As important as their goals may be, social justice, critical methodologies, or approaches that decenter settler perspectives have objectives that may be incommensurable with decolonization. Because settler colonialism is built upon an entangled triad structure of settler-native-slave, the decolonial desires of white, non-white, immigrant, postcolonial, and oppressed people, can similarly be entangled in resettlement, reoccupation, and reinhabitation that actually further settler colonialism. The metaphorization of decolonization makes possible a set of evasions, or “settler moves to innocence”, that problematically attempt to reconcile settler guilt and complicity, and rescue settler futurity. In this article, we analyze multiple settler moves towards innocence in order to forward “an ethic of incommensurability” that recognizes what is distinct and what is sovereign for project(s) of decolonization in relation to human and civil rights based social justice projects. We also point to unsettling themes within transnational/Third World decolonizations, abolition, and critical space-place pedagogies, which challenge the coalescence of social justice endeavors, making room for more meaningful potential alliances
Keywords: 1-Cinéma; 1-Histoire de l'art; 1-Jeux vidéo; 1-TV; 2-Méthodologie de recherche décoloniale; 2-Pédagogie décoloniale; 2-Théories et épistémologie postcoloniales et décoloniales; 2-Épistémologies autochtones; 3-Amérique du Nord (corpus analysé); 4-Amérique du Nord (lieu de production du savoir); 5-Auteur.rice autochtone; 5-Autrice; _Nettoyé

Indigenous Methodologies: Characteristics, Conversations, and Contexts - Kovach, Margaret (University of Toronto Press, 2009)
"An innovative and important contribution to Indigenous research approaches, this revised second edition provides a framework for conducting Indigenous methodologies, serving as an entry point to learn more broadly about Indigenous research."--
Keywords: 2-Méthodologie de recherche décoloniale; 2-Pédagogie décoloniale; 2-Théories et épistémologie postcoloniales et décoloniales; 3-Amérique du Nord (corpus analysé); 4-Amérique du Nord (lieu de production du savoir); 5-Auteur.rice autochtone; 5-Autrice; _Nettoyé